Input-Output Budget of Nitrogen and the Effect of Experimentally Changed Deposition in the Forest Ecosystems in Central Japan - Junko Shindo; Tamon Fumoto; Noriko Oura; Hideshige Toda; Hiroyuki Kawashima (The Scientific World Journal)
To evaluate the current nitrogen (N) status in Japanese forests, field measurements of rainfall, throughfall, litter layer percolation, and soil solution percolation were conducted in a red pine stand (Kannondai) and a deciduous stand (Yasato) located in central Japan. N input via throughfall was 31 and 14 kg ha–1 year–1and output below rooting zone was 9.6 and 5.5 kg ha1 year–1 in Kannondai and in Yasato, respectively. Two thirds of input N were retained in plant-soil systems. Manipulation of N input was carried out. Ionic constituents were removed from throughfall with ion exchange resin at removal sites and ammonium nitrate containing twice the N of the throughfall was applied at N addition sites periodically. SO42– output below 20-cm soil layer changed depending on the input, while NO3– output was regulated mainly by the internal cycle and effect of manipulation was undetected. These Japanese stands were generally considered to have a larger capacity to assimilate N than NITREX sites in Europe. However, N output fluxes had large spatial variability and some sites in Kannondai showed high N leaching below rooting zone almost balanced with the input via throughfall.